Perioperative Management of Antithrombotic Therapy: An American College of Chest Physicians Clinical Practice Guideline - Douketis, James D; Spyropoulos, Alex C; Murad, M Hassan; Arcelus, Juan I; Dager, William E; Dunn, Andrew S; Fargo, Ramiz A; Levy, Jerrold H; Samama, C Marc; Shah, Sahrish H; Sherwood, Matthew W; Tafur, Alfonso J; et al. (Chest, 2022)
The American College of Chest Physicians Clinical Practice Guideline on the Perioperative Management of Antithrombotic Therapy addresses 43 Patients-Interventions-Comparators-Outcomes (PICO) questions related to the perioperative management of patients who are receiving long-term oral anticoagulant or antiplatelet therapy and require an elective surgery/procedure. This guideline is separated into four broad categories, encompassing the management of patients who are receiving: (1) a vitamin K antagonist (VKA), mainly warfarin; (2) if receiving a VKA, the use of perioperative heparin bridging, typically with a low-molecular-weight heparin; (3) a direct oral anticoagulant (DOAC); and (4) an antiplatelet drug. Strong or conditional practice recommendations are generated based on high, moderate, low, and very low certainty of evidence using the Grading of Recommendations, Assessment, Development, and Evaluation (GRADE) methodology for clinical practice guidelines. A multidisciplinary panel generated 44 guideline recommendations for the perioperative management of VKAs, heparin bridging, DOACs, and antiplatelet drugs, of which two are strong recommendations: (1) against the use of heparin bridging in patients with atrial fibrillation; and (2) continuation of VKA therapy in patients having a pacemaker or internal cardiac defibrillator implantation. There are separate recommendations on the perioperative management of patients who are undergoing minor procedures, comprising dental, dermatologic, ophthalmologic, pacemaker/internal cardiac defibrillator implantation, and GI (endoscopic) procedures. Substantial new evidence has emerged since the 2012 iteration of these guidelines, especially to inform best practices for the perioperative management of patients who are receiving a VKA and may require heparin bridging, for the perioperative management of patients who are receiving a DOAC, and for patients who are receiving one or more antiplatelet drugs. Despite this new knowledge, uncertainty remains as to best practices for the majority of perioperative management questions.